A FLEXIBILIZAÇÃO DO ENSINO SUPERIOR COMO UM FENÔMENO DA SOCIEDADE DO CONHECIMENTO. - Moraes, Bianca de França Tempone Felga de (2004)
The present paper aims to analyze the graduate teaching in Brazil, focusing the flexibility of the graduate studies and its reflex on the society of knowledge. There is a clear intention to show that the flexibility of the graduate teaching helps the courses to fulfill the demands of knowledge and contributes to the changes of behaviorofsociety. This teaching flexibility should not be considered as a deformation of an existing ideal, elitist model of teaching, but as a fundamental and essential component of the popular graduate education, typical of the modern world and of the society of knowledge. The result of these transformations in this society would be a new reality, typically Brazilian, with the characteristics of the country's most known profile: huge, complex, contradictory, flexible, uneven, dynamic, creative and in progression.